2008
DOI: 10.1001/archpsyc.65.9.1017
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis, Database, and Meta-regression of 98 Structural Imaging Studies in Bipolar Disorder

Abstract: The meta-analyses revealed robust but regionally nonspecific changes of brain structure in bipolar disorder. Individual studies will remain underpowered unless sample size is increased or improvements in phenotypic selection and imaging methods are made to reduce within-study heterogeneity. The provision of online databases, as illustrated herein, may facilitate a more refined design and analysis of structural imaging data sets in bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
355
1
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 496 publications
(405 citation statements)
references
References 164 publications
33
355
1
16
Order By: Relevance
“…Thus, while schizophrenia is characterized by a reduction in whole volume of around 2%, coupled with larger reductions in regions such as the frontal lobe and the hippocampus 15, bipolar disorder appears to be associated with only at most minor whole brain and regional volume changes 16, 17. Few studies have examined schizoaffective disorder using conventional CT or MRI measures 18, 19, 20, 21, and these have mostly been underpowered and have not demonstrated clear differences from either schizophrenia or bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while schizophrenia is characterized by a reduction in whole volume of around 2%, coupled with larger reductions in regions such as the frontal lobe and the hippocampus 15, bipolar disorder appears to be associated with only at most minor whole brain and regional volume changes 16, 17. Few studies have examined schizoaffective disorder using conventional CT or MRI measures 18, 19, 20, 21, and these have mostly been underpowered and have not demonstrated clear differences from either schizophrenia or bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…BD has also been coupled to cognitive impairment including reduced abilities in executive function and verbal memory (Martinez-Aran et al, 2000;Zarate et al, 2000;Martinez-Aran et al, 2005;Robinson et al, 2006;Sanchez-Moreno et al, 2009;Palsson et al, 2013). Structural imaging studies have suggested that the decline in cognitive function is associated with morphological abnormalities of the brain (Altshuler et al, 1995;McDonald et al, 2004;Kempton et al, 2008;Konarski et al, 2008), and that the number of manic episodes is associated with decreased gray matter in dorsolateral prefrontal cortex (Ekman et al, 2010). The most frequent abnormal morphological findings are lateral ventricular enlargements and increased rates of deep white matter hyperintensities (Kempton et al, 2008;Beyer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Structural imaging studies have suggested that the decline in cognitive function is associated with morphological abnormalities of the brain (Altshuler et al, 1995;McDonald et al, 2004;Kempton et al, 2008;Konarski et al, 2008), and that the number of manic episodes is associated with decreased gray matter in dorsolateral prefrontal cortex (Ekman et al, 2010). The most frequent abnormal morphological findings are lateral ventricular enlargements and increased rates of deep white matter hyperintensities (Kempton et al, 2008;Beyer et al, 2009). The association between white matter pathology and BD has been further supported by morphometric studies showing reductions in total white matter volumes (Strakowski et al, 1993;Kieseppa et al, 2003;Davis et al, 2004;Rosso et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lateral ventricular enlargement has been a regular finding in studies of bipolar disorder and is supported by meta-analyses (Arnone et al, 2009, Kempton et al, 2008.…”
Section: Neuroimaging Structural Imaging Studies In Schizoaffective Dmentioning
confidence: 83%
“…However, these meta-analyses found only small effect sizes for whole brain volume reduction, which were significant in one (Arnone et al, 2009) but not in the other (Kempton et al, 2008). In contrast, studies using VBM have found more consistent evidence of abnormality, which affect principally the anterior cingulate cortex, insula and inferior frontal cortex (Bora et al, 2010, Selvaraj et al, 2012.…”
Section: Neuroimaging Structural Imaging Studies In Schizoaffective Dmentioning
confidence: 85%